Involvement of CYP347W1 in neurotoxin 3‐nitropropionic acid‐based chemical defense in mustard leaf beetle Phaedon cochleariae. (17th September 2021) - Fu, Nanxia; Becker, Tobias; Brandt, Wolfgang; Kunert, Maritta; Burse, Antje; Boland, Wilhelm
Abstract: Chrysomelina beetlesstore 3‐nitropropionic acid in form of a pretoxin, isoxazolin‐5‐one glucoside‐conjugated ester, to protect themselves against predators. Here we identified a cytochrome P450 monooxygenase, CYP347W1, to be involved in the production of the 3‐nitropropionic acid moiety of the isoxazolin‐5‐one glucoside ester. Knocking down CYP347W1 led to a significant depletion in the concentration of the isoxazolin‐5‐one glucoside ester and an increase in the concentration of the isoxazolin‐5‐one glucoside in the larval hemolymph. Enzyme assays with the heterologously expressed CYP347W1 showed free β ‐alanine was not the direct substrate. Homology modeling indicated that β ‐alanine‐CoA ester can fit into CYP347W1 's active site. Furthermore, we proved that Phaedon cochleariae eggs are not able to de novo synthesize 3‐NPA, although both isoxazolin‐5‐one glucoside and its 3‐NPA‐conjugated ester are present in the eggs. These results provide direct evidence for the involvement of CYP347W1 in the biosynthesis of a P. cochleariae chemical defense compound. Abstract : Chrysomelina beetles store 3‐nitropropionic acid in form of a pretoxin, isoxazolin‐5‐one glucoside‐conjugated ester, to protect themselves against predators. Here we identified a cytochrome P450 monooxygenase, CYP347W1, to be involved in the production of the 3‐nitropropionic acid moiety of the isoxazolin‐5‐one glucoside ester. Knocking down CYP347W1 led to a significant depletion in the concentration of the isoxazolin‐5‐one glucoside ester and an increase in the concentration of the isoxazolin‐5‐one glucoside in the larval hemolymph. Enzyme assay with the heterologously expressed CYP347W1 showed free β‐alanine was not the direct substrate.